STUDI KELAYAKAN PENGEMBANGAN INVESTASI PADA RUMAH SAKIT GIGI DAN MULUT FKG UNIVERSITAS MAHASARASWATI DENPASAR - Adi Arwati, Ni Ketut; Panji Sedana, Ida Bagus; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Oral health can be achieved if optimum available infrastructure is adequate. Dental Hospital is one means of oral health care advanced, and provide quality services in an integrated manner and according to the demands of society and the development technological science of dentistry. The objective of this research  was to determine the feasibility of the development of investment in the Dental Hospital Faculty of Dentistry, University of Mahasaraswati Denpasar through the analysis of the feasibility of the business in terms of aspects of the market and financial aspects. Market and marketing aspects of using the potential of the market, while the financial aspects analyzed by Method Payback Period, Net Present Value and Internal Rate of Return. Results of the analysis of aspects of the market shows that an increase in patient visits the teeth and mouth from 2015 to 2019, while the results of the analysis of the financial aspects in moderate condition indicates that : Payback Period is lower than the life of the project (5 years) that is 2 years, 2 months and 53 days; Positive Net Present Value of Rp 1,677,298,073; Internal Rate of Return 56.70% greater than the opportunity cost is 7%. In the pessimistic conditions: Payback Period: 1 year, 2 months and 23 days; Positive Net Present Value of Rp 1,341,838,458; Internal Rate of Return 50.44% greater than the opportunity cost and in a state of optimistic: Payback Period is lower than the life of the project (5 years) is 1 year, 2 months and 28 days; Net Present Value of Rp 2,012,757,690; Internal Rate of Return 56,96% greater than the opportunity cost is 7%.
Keywords: Feasibility Study, the Dental Hospital Faculty of Dentistry Investment Development Mahasaraswati University Denpasar.